2011
DOI: 10.3892/ijo.2011.909
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyflutamide enhances cellular sensitivity to 5-fluorouracil by suppressing thymidylate synthase expression in bicalutamide-resistant human prostate cancer cells

Abstract: Abstract.We investigated the antitumor effects of combination therapy with anti-androgens and 5-fluorouracil (5-FU), and examined the underlying mechanism of the treatment. Initially, we established the bicalutamide-resistant subline CDX25R from the androgen receptor (AR)-positive human prostate cancer cell line LNCaP through continuous exposure to bicalutamide. CDX25R cells lost the ability to respond to androgens, but still expressed AR. They showed significant resistance to bicalutamide, but had high sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…To generate bicalutamide-resistant cells and enzalutamide-resistant cells, the LNCaP cells, one of the androgen-dependent prostate cancer cell strains, were treated with enzalutamide (10 μ M) ( 32 ) and bicalutamide (10 μ M) (Selleck Chemicals, Houston, TX, USA), respectively for at least 6 months. For the generation of bicalutamide-resistant (Bica-R) cells, the cells were first cultured with 1 μ M ( 33 ), or 5, 10 or 25 μ M ( 34 ) bicalutamide, respectively. We found that the concentration of 1 μ M bicalutamide had almost no effect on the LNCaP cells, and the concentration of 25 μ M bicalutamide killed too many cells to induce the cells continually (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…To generate bicalutamide-resistant cells and enzalutamide-resistant cells, the LNCaP cells, one of the androgen-dependent prostate cancer cell strains, were treated with enzalutamide (10 μ M) ( 32 ) and bicalutamide (10 μ M) (Selleck Chemicals, Houston, TX, USA), respectively for at least 6 months. For the generation of bicalutamide-resistant (Bica-R) cells, the cells were first cultured with 1 μ M ( 33 ), or 5, 10 or 25 μ M ( 34 ) bicalutamide, respectively. We found that the concentration of 1 μ M bicalutamide had almost no effect on the LNCaP cells, and the concentration of 25 μ M bicalutamide killed too many cells to induce the cells continually (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of patients were switched from bicalutamide to flutamide after they relapsed from the initial hormonal therapy in this study. We recently established a bicalutamide-resistant prostate cancer subline, CDX25R, and demonstrated that the combined treatment of 5-FU and hydroxyflutamide (OH-flutamide), the active metabolite of flutamide, had a synergistic effect on CDX25R cells (21). In addition, we found that OH-flutamide decreased the expression of the E2F1 transcription factor followed by a decreased TS expression in CDX25R cells as the underlying mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…The suppression of downstream genes such as transcription factor E2F1 and thymidylate synthase was identified as the key driver of inhibition of the growth of resistant cells. 26…”
Section: ■ Increased Ar Expressionmentioning
confidence: 99%
“…In one study, a combination of flutamide with a chemotherapy agent, 5-fluorouracil, which is an analogue of a pyrimidine base, was capable of inducing apoptosis following an arrest in DNA biosynthesis in bicalutamide-resistant cells. The suppression of downstream genes such as transcription factor E2F1 and thymidylate synthase was identified as the key driver of inhibition of the growth of resistant cells …”
Section: Increased Ar Expressionmentioning
confidence: 99%